Playing with the social network: Social cohesion in resettled and non-resettled communities in Cambodia - Simone Gobien; Björn Vollan (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2013)
Mutual aid among villagers in developing countries is often the only means of insuring against economic shocks. We use "lab-in-the-field experiments" in Cambodian villages to study social cohesion in established and newly resettled communities. Both communities are part of a land distribution project. The project participants all signed up voluntarily, and their socio-demographic attributes and pre-existing network ties are similar. We use a version of the "solidarity game" to identify the effect of voluntary resettlement on willingness to help fellow villagers after an income shock. We find a sizeable reduction in willingness to help others. Resettled players transfer on average between 47% and 74% less money than non-resettled players. The effect remains large and significant after controlling for personal network and when controlling for differences in transfer expectations. The costs of voluntary resettlement, not only monetary but also social, seem significantly higher than is commonly assumed by development planners.
Keywords: C93; O15; O22; R23; 330; Voluntary resettlement; Social cohesion; Risk-sharing networks; Monetary transfers; "Lab-in-the-field"experiment; Cambodia; Umsiedlung; Soziale Folgen; Intergenerationale Übertragung; Soziales Netzwerk; Kambodscha; Test